2015
DOI: 10.1186/s12931-015-0231-5
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of a Protein Epitope Mimetic CCR10 antagonist, POL7085, in a model of allergic eosinophilic airway inflammation

Abstract: BackgroundPotential involvement of the CCR10/CCL28 axis was recently reported in murine models of allergic asthma. If confirmed, blockade of the CCR10 receptor would represent an alternative to current asthma therapies. We evaluated the effect of a novel Protein Epitope Mimetic CCR10 antagonist, POL7085, in a murine model of allergic eosinophilic airway inflammation.MethodsMice were sensitized and challenged to ovalbumin. POL7085, a CCR10 antagonist (7.5 and 15 mg/kg), dexamethasone (1 mg/kg) or vehicle were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…Some recently identi ed biomarkers of CRSwNP, for example CST1 [41], were also found to be differentially expressed between CRSwNP+AS and CRSwNP-alone. Importantly, the present study showed that some of the most signi cant DE-mRNAs; including ITLN1, KCNA3 and CCR10; which were up-regulated in nasal tissue of CRSwNP+AS compared to nasal tissue of CRSwNP-alone (Additional le 1: Figure S8), are also expressed in the bronchial tissue and contribute to the pathogenesis of asthma [42][43][44]. This suggests that signature genes identi ed in nasal tissue of CRSwNP+AS might also play important roles in the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 66%
“…Some recently identi ed biomarkers of CRSwNP, for example CST1 [41], were also found to be differentially expressed between CRSwNP+AS and CRSwNP-alone. Importantly, the present study showed that some of the most signi cant DE-mRNAs; including ITLN1, KCNA3 and CCR10; which were up-regulated in nasal tissue of CRSwNP+AS compared to nasal tissue of CRSwNP-alone (Additional le 1: Figure S8), are also expressed in the bronchial tissue and contribute to the pathogenesis of asthma [42][43][44]. This suggests that signature genes identi ed in nasal tissue of CRSwNP+AS might also play important roles in the pathogenesis of asthma.…”
Section: Discussionmentioning
confidence: 66%
“…Regarding effector T cells, they are known to rely on their CCR6 receptor, which binds the CCL20 chemokine produced by corneal and conjunctival epithelial cells, to home to the OS . Hence, the strategy of blocking CCL20 by topical instillation of anti‐CCL20 antibody to ameliorate murine DED is intriguing, and is akin to successful approaches explored in other mucosal surfaces …”
Section: Mucosal Immune Tolerance In Os Diseasementioning
confidence: 99%
“…35,126 Hence, the strategy of blocking CCL20 by topical instillation of anti-CCL20 antibody to ameliorate murine DED is intriguing, 35 and is akin to successful approaches explored in other mucosal surfaces. 127 Finally, the ocular microbiome has become a hot research topic. Whether there is a stable microbiota in every OS is still subject to debate, but evidence is accumulating on the changes in microbial diversity in the context of eye disease.…”
Section: Therapeutic Manipulation Of Ocular Mucosal Tolerancementioning
confidence: 99%
“…The rs6870783, which is located at 60 kb from CCL28 and 50 kb away from PAIP1 (encoding the poly(A)-binding protein-interacting protein 1), evidenced a protective effect for asthma susceptibility for its minor allele (G allele) in both the GWAS discovery (OR = 0.94, 95% CI = 0.91-0.98, P = 8.99 9 10 À4 ) and in the replication study (OR = 0.85, 95% CI = 0.73-0.98, P = 0.029). However, despite the suggested role of CCL28 as a chemokine for eosinophil recruitment to peribronchial regions of the lung [32], this finding was not significant in the context of the multiple tests performed (threshold for significance at P < 0.05/14 = 0.0036). The three SNPs assigned to FZD6 have moderate (r 2 = 0.51) or strong LD (r 2 = 0.99) between each other and similar effect sizes, irrespective of the study.…”
Section: Resultsmentioning
confidence: 77%